2018
DOI: 10.1111/ctr.13410
|View full text |Cite
|
Sign up to set email alerts
|

Association between the “Timed Up and Go Test” at transplant evaluation and outcomes after kidney transplantation

Abstract: The TUGT was not associated with waitlist removal or prolonged hospitalization for kidney transplant candidates. Alternative assessments of global health, such as functional status or frailty, should be considered for evaluation of potential kidney transplant candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
8
3
Order By: Relevance
“…However, in this present study, failing TUGT was associated with an unfavorable transplant waitlist evaluation outcome (OR 2.14, CI 95% 1.43–3.19, p < .001). The discrepancy from this present study and Michelson et al is likely due to the difference in cutoff time points for TUGT, which are age‐dependent 23,24 . Michelson et al segregated TUGT times as short (<8 s), average (8–9 s), and long >9 (s) and demonstrated a clear association between TUGT time and age.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…However, in this present study, failing TUGT was associated with an unfavorable transplant waitlist evaluation outcome (OR 2.14, CI 95% 1.43–3.19, p < .001). The discrepancy from this present study and Michelson et al is likely due to the difference in cutoff time points for TUGT, which are age‐dependent 23,24 . Michelson et al segregated TUGT times as short (<8 s), average (8–9 s), and long >9 (s) and demonstrated a clear association between TUGT time and age.…”
Section: Discussioncontrasting
confidence: 92%
“…TUGT is a validated screening tool for frailty and peri‐operative outcomes that assesses functional mobility, muscle strength, coordination, and physical performance in surgical patients 26–34 . TUGT was previously examined by Michelson et al in renal transplantation patients and was not associated with transplant waitlist removal or post‐transplant outcomes 23 . However, in this present study, failing TUGT was associated with an unfavorable transplant waitlist evaluation outcome (OR 2.14, CI 95% 1.43–3.19, p < .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported functional status, for example, has been found to be associated with post-KT mortality (25). However, other objective measures like the Timed-up-and-go Test was not associated with post-KT length of stay, or early hospital readmission (55). Additionally, lower extremity impairment, objectively measured by the short physical performance battery (SPPB), is present in 48% of KT recipients (56).…”
Section: Alternative Measures Of Vulnerability and Long-term Post-kt mentioning
confidence: 99%
“…Nonetheless, there is a compelling case for performing an FP assessment in those screened as at risk of frailty, given the numerous studies that have demonstrated an association between frailty, as identified by the FP, and post-transplant outcomes (28,35). Simpler measures, such as walking speed or the Timed Up and Go Test, do not seem be as good of a predictor of outcomes (44,45). Schaenman et al (46) performed a pilot study evaluating the feasibility and utility of a simple chart review-based Frailty Risk Score (FRS) to predict post-transplant outcomes.…”
Section: How Should Frailty Be Identified In the Potential Kidney Tramentioning
confidence: 99%